EFFECT OF PROBIOTIC ON THE GUT MICROFLORA AND HEMATOLOGICAL PARAMETERS OF CROSSBRED PIGS (Indian Journal of Animal Production and Management, 2013)
Disease not only affects animal health and well being, but also the economy of the producers. Works on effect of probiotic in pigs have been conducted, however information regarding effect of Sacchromyces cervisiae feeding on crossbred early weaned piglets is lacking. Therefore, the experiment was designed to assess the effect of probiotic (Saccharomyces cervisiae) on the coliform count and hematological parameters of crossbred weaned pigs. A total of 24 weaned crossbred piglets were selected and distributed randomly in four groups comparising of six in each. Saccharomyces cerivisae had been added at level of 0.25%, 0.50% and 1 % in T2, T3 and T4 groups, respectively and T1 was taken as control group. Fecal samples of all the groups were examined for total coliform count at 0, 45th and at 90th days. For Red blood cells (RBC) count, White blood cells (WBC) count, Lymphocytes (LYM) %, Granulocyte (GRAN) %, Hemoglobin (HG), Hematocrit (HCT)% and total platelets (PLT) count, blood was collected at monthly interval. Coliform count (x 103/gm) was significantly lower (P0.05) difference in all haematological parameters among different group at different time interval.
Keywords: Probiotic; Coliform Count; Blood profile; Gut micro flora; Saccharomyces cervisiae